Student experience of using mobile devices for learning chemistry - Wai Foong Lok; Mahizer Hamzah (Institute of Advanced Engineering and Science, 2021)
Mobile devices have been utilized as an emerging learning tool in the 21st century to support the learning of chemistry. This study aimed to identify matriculation students’ learning experience with regards to the use of mobile devices for learning chemistry. The study employed a qualitative case study approach, which was carried out in a matriculation college. Online diaries and interviews were utilized as the instruments of the study. A total of 84 students initially reflected their learning journey using an online diary, whereas 17 students who were active in mobile learning were purposely selected for the interview. The findings revealed that students have positive and negative experiences towards the use of mobile devices for learning chemistry. They positively perceived that using a mobile device for learning chemistry promotes knowledge construction, visualization of abstract concepts, self-control in learning and intellectual discourse. However, the issue of learning resources quality challenged their available cognitive capacity for learning chemistry. This study offered educators with insights about the importance of incorporating mobile devices for learning chemistry. Educators can plan the appropriate instructional strategies for chemistry based on the students’ learning needs.